Propagating totalitarism and inciting to hatred under article 256 of the Penal Code - Radziejewski, Piotr (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The paper deals with the provision of Article 256 of the Polish Penal Code. The author discusses the offences of public propagation of totalitarian forms of government, and offence of inciting to hatred on national, ethnic, racial or religious grounds and offences connected with objects with such content. The author pays particular attention to the controversial and unclear wording used in the above regulation and identifies possible amendments that could make the article more precise and effective.